Female Greater Prairie‐Chicken response to energy development and rangeland management. Issue 12 (9th December 2019) - Londe, David W.; Fuhlendorf, Samuel D.; Elmore, R. Dwayne; Davis, Craig A.; Rutledge, Jimmy
Abstract: Wildlife habitat use is the result of behaviors that occur at multiple spatial and temporal scales. The interactions between these behaviors can often result in complex patterns of selection that can make it challenging to select the most appropriate scale to implement management actions. Greater Prairie‐Chickens ( Tympanuchus cupido ), a declining grassland grouse species, face many conservation challenges throughout its distribution, including increased fragmentation from anthropogenic activities (e.g., energy development and altered disturbance regimes). However, much of the literature on this species has focused on a narrow portion of its lifecycle, specifically the breeding season. We examined habitat use of female Greater Prairie‐Chickens in a grassland that is managed with prescribed fire and grazing and that has also undergone considerable development for oil and gas production. We developed discrete choice models for four behaviorally distinct life‐history stages and two spatial scales to evaluate how rangeland management, energy development, and scale influence habitat use throughout the annual cycle. Additionally, we used cumulative distribution functions to determine response distances to landscape features. We found that time since fire, proximity to woodlands and proximity of lek sites were the most consistent predictors of habitat use during most periods and spatial scales. Greater Prairie‐Chickens consistently avoided woodlands and remained relatively close to lek sites during all parts of the year. Selection of time since fire varied through the year with Greater Prairie‐Chickens primarily using unburned patches in the lekking and nesting season and recently burned patches in the post‐nesting and nonbreeding season. Greater Prairie‐Chickens demonstrated a seasonally variable response to energy development, avoiding power lines and areas with a high densities of oil wells by as much as 300–600 m in the lekking, post‐nesting, and nonbreeding season. Management actions that promote vegetation heterogeneity will benefit Greater Prairie‐Chickens by creating a variety of seral stages used during different life stages, but efforts should be made to limit future fragmentation of grasslands by energy development.